Drying Kinetics and Changes of Total Phenolic Content, Antioxidant Activity and Color Parameters of Mango and Avocado Pulp in Refractance Window Drying - Thi-Van-Linh Nguyen; Quoc-Duy Nguyen; Phuoc-Bao-Duy Nguyen (Polish Journal of Food and Nutrition Sciences)
Refractance window drying is an innovative technology belonging to the fourth generation of drying technologies that could enhance the quality of the dried product and improve the drying process. In this study, two factors with the type of fruit pulps (avocado and mango) and drying temperature (ranging from 80 to 95°C) were investigated. Results showed that in refractance window drying, the evaporation process rapidly occurred, mainly in the falling-rate period with undetectable the constant-rate period. The Weibull was the best fit model among eight investigated mathematical models that could determine the drying behavior. The effective diffusivity was found to be from 4.25x10 -10 m 2 /s to 7.24x10 -10 m 2 /s for avocado pulp, and from 4.50x10 -10 m 2 /s to 10.67x10 -10 m 2 /s for mango pulp when the drying temperature was changed from 80 to 95°C. Moreover, the corresponding activation energy was 32.06 and 66.03 kJ/mol for avocado and mango pulp moisture evaporation, respectively, and the highest quality of powders of both dried pulps was obtained after processing at 90°C. The refractance window drying revealed a high potential in the production of fruit powders from avocado and mango due to the high retention of more than 80% of total phenolic content (TPC) and antioxidant activity. TPC could be used as a useful criterion for the evaluation of the drying process in terms of dried product quality.